Vainglorious Poetry (Syi'r al-Fakhr wa al-Hamasa) of the Umayyad Rulers of al-Andalus A Textual Thematic Examination - Hasan, Ahmad (Penerbit Universiti Malaysia Pahang, 2009)

(untitled)
The Umayyad rulers of al-Anda/us; were professional poets to some extent. The extensive study on the poetry of the Umayyad shows that, on one hand, more than 200 couplets of poetry found to be composed by the rulers themselves according to Ibrahim Baydun in his book al-Shi 'r al-Amiri fi al-Anda/us (The Emirite Poetry in Andalusia). On the other hand, those poetic compositions in the forms of poetry and prose have shown many poetic qualities in many areas of Arabic rhetorical studies. Moreover, the Umayyad ruler-poets had also composed poetry on many popular themes and one of the most significant is the vainglory. Being approached through extensive hermeneutical tools, the study reveals the comprehensive employment of the vainglorious theme by many Umayyad rulers such as al-Dakhil and al-Rabadi. According to authoritative Andalusian sources, both had produced some 67 couplets of poetry during their life which many of them employing the theme of vainglory. This makes the vainglory the most popular Arabic literary genre employed amongst the ruler-poets of al-Anda/us.